Sosialisasi dan Edukasi Kesehatan Reproduksi bagi Remaja di SMA Yapim Biru-Biru - Fahdi, Firdaus; Sari, Herviani; Manullang, Hengki Frengki; Sembiring, Bungamari (INSTITUT KESEHATAN DELI HUSADA, 2024)
Adolescence is a critical period in a person's life, marked by significant physical, emotional, and social changes. Adequate knowledge about reproductive health is essential to help adolescents face these changes in a healthy and positive way. However, the spread of formal education and the stigma surrounding this topic often results in low understanding and risky behavior among teenagers. The